Bequests, Control Rights, and Cost-Benefit Analysis - Amihai Glazer; Vesa Kanniainen; Esko Niskanen (Center for Economic Studies and ifo Institute (CESifo), 2001)
Consider a public project which produces a consumption good and which benefits future generations. Let a conventional cost-benefit analysis find that it gives higher benefits than projects it would dis-place in the private sector. Voters may nevertheless oppose the public project: the combination of a desire to control bequests and the lack of control over who gets benefits from a public project makes the public project unattractive. In contrast, private projects have owners, allowing parents to control whether their children will receive the benefits from such projects. Parents can therefore better influence the behavior of their children when they have the option of giving the children title to private projects.
Keywords: 330; public projects; cost-benefit analysis